Development of Water Pop-Up Book Media with a Scientific Approach: Efforts to Increase Elementary Students' Scientific Literacy - Moch Bayu Ibrahim S; Nurlela Nurlela; M Burhan Rubai Wijaya; Bambang Subali (Universitas Negeri Semarang, 2022)
This research develops the water pop-up book media with a scientific approach. The purposes of this study were to describe the development of the water pop-up book media and to test the effectiveness of the media in increasing scientific literacy. The research method used was 4D research and development with the Define, Design, Development, and Dissemination stages. Limited trial subjects consisted of 20 students, and product trials consisted of 60 students. The results of the study showed that the media based on the feasibility assessment by experts and the readability test were included in the excellent category. The use of Pop-Up Book media is effective. This can be seen from the results of learning by using literacy-based questions in the pretest and posttest, which got an average difference of 16.08. The results of the t-test obtained an average increase of 0.448, which were included in the medium criteria, so the pop-up book media with a scientific approach was very valid and effective when used in learning.